Dilatation of the Endolymphatic Space in the Ampulla of the Posterior Semicircular Canal: A New Clinical Finding Detected on Magnetic Resonance Imaging. Issue 6 (July 2021) - Morioka, Masaru; Sugimoto, Satofumi; Yoshida, Tadao; Teranishi, Masaaki; Kobayashi, Masumi; Nishio, Naoki; Katayama, Naomi; Naganawa, Shinji; Sone, Michihiko
Abstract : Objectives: To investigate the clinical features of ears with dilatation of the endolymphatic space in the ampulla of the posterior semicircular canal on magnetic resonance imaging. Study Design: Retrospective study. Setting: A university hospital. Methods: This study included 1, 842 ears from 934 patients who underwent 3-T magnetic resonance imaging with gadolinium to investigate the presence of endolymphatic hydrops. Age, sex distribution, hearing thresholds on pure-tone audiometry, and vestibular symptoms were compared between cases of unilateral and bilateral dilatation of the endolymphatic space in the ampulla of the posterior semicircular canal. Results: Forty-eight ears (17 men and 14 women; mean age 49.9 yrs) showed dilatation of the endolymphatic space in the ampulla of the posterior semicircular canal. Age and the rate of chronic sensorineural hearing loss were significantly higher in the unilateral group (14 ears) than in the bilateral group (34 ears). The average hearing thresholds and rates of vestibular symptoms reported did not differ between unilateral and bilateral cases, but some patients showed positional nystagmus. Conclusions: Dilatation of the endolymphatic space in the ampulla was observed selectively in the posterior semicircular canal, though its pathogenesis was not clear. Such dilatation is not usually accompanied by vestibular endolymphatic hydrops, and it may be a cause of vertigo and dizziness.